Bem estar subjetivo e efeito de idade em notas padronizadas : uma análise do PISA 2018 - Esidio, Emilly Cavalheiro (2021)
This work is composed by two essays that focus on the themes of educational outcome of the participating students caused by entry school age and of the students’ subjective wellbeing, using for that different econometric tools. For that, the database from the 2018 Programme for International Student Assessment (PISA) is used for both papers. The first evaluates the effects of the school entry age over the students performance in mathematics, science and reading, using a instrumental variables approach. The results indicate a better performance from the students that joined school at a later age, for all disciplines. In the second essay, the three dimensions of wellbeing – life satisfaction, positive effect and negative effect are estimated through Exploratory Factor Analysis. The paper then further explores differences between genres on the three forementioned dimensions of wellbeing. The estimates indicate a lower level of subjective wellbeing on girls for the positive effect and negative effect aspects when compared to their male counterparts.